2009
DOI: 10.1158/0008-5472.sabcs-09-2019
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Molecular Subtypes Predict Response to Anthracycline/Taxane-Based Chemotherapy.

Abstract: Background: Classifying breast cancer into molecular subtypes (Luminal A/B, Her2-enriched, and Basal-like) has proven to be biologically and clinically informative. Recently, we developed a gene expression based protocol (PAM50) that provides reliable subtype classification as well as independent prognostic utility (Parker et al, J Clin Oncol 2009). In this study, we evaluated the ability of the PAM50 subtypes to predict pathological complete response (pCR) to anthracycline/taxane-based chemotherapy in the neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…Meanwhile, the luminal B group had Abbreviations: ER, estrogen receptor; HER-2, human epidermal growth factor receptor; VEGF, vascular endothelial growth factor. an appreciable pCR rate, but it was still rather low (Table 1) [12].…”
Section: Therapeutic Targets For Basal-like Breast Cancermentioning
confidence: 94%
“…Meanwhile, the luminal B group had Abbreviations: ER, estrogen receptor; HER-2, human epidermal growth factor receptor; VEGF, vascular endothelial growth factor. an appreciable pCR rate, but it was still rather low (Table 1) [12].…”
Section: Therapeutic Targets For Basal-like Breast Cancermentioning
confidence: 94%
“…Several studies have suggested that luminal-B breast cancer was relatively insensitive to endocrine therapy compared to luminal-A breast cancer and to paclitaxeland doxorubicin-containing preoperative chemotherapy compared with HER2-positive and basal-like breast cancers. However, luminal-B breast cancer responds better to neoadjuvant chemotherapy than luminal-A subtype, achieving higher pathological complete response rates [25][26][27][28][29] . Increased relapse rates observed in luminal-B tumors are limited to the first 5 years after diagnosis [30] .…”
Section: Luminal-bmentioning
confidence: 99%
“…Since 2009, the PAM50 subtype predictor has shown to provide prognostic and predictive value across multiple cohorts of patients with breast cancer (8,(9)(10)(11)(12)(13). For example, two studies have shown that the PAM50 subtype predictor predicts pathologic complete response (pCR) after neoadjuvant anthracycline-taxane-based chemotherapy (8,14).…”
Section: Introductionmentioning
confidence: 99%